2022
DOI: 10.3390/v14091951
|View full text |Cite
|
Sign up to set email alerts
|

Serological Response and Clinical Protection of Anti-SARS-CoV-2 Vaccination and the Role of Immunosuppressive Drugs in a Cohort of Kidney Transplant Patients

Abstract: Vaccination against SARS-CoV2 represents a key weapon to prevent COVID-19, but lower response rates to vaccination have frequently been reported in solid organ transplant recipients. The aim of our study was to evaluate the rate of seroconversion to SARS-CoV-2 mRNA vaccines in a cohort of kidney transplant recipients and the potential role of the different immunosuppressive regimens. We conducted an observational retrospective cohort study in kidney transplant patients vaccinated for COVID-19. For each patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Nevertheless, this beneficial effect of mTORi after two doses of vaccine was no maintained in the adjusted model in our cohort, findings also noted by Bae ( 33 ). Several authors found similar results with MPA and mTORi in different groups of patients who received two doses ( 33 37 ), even proposing the temporary suspension of treatment during the vaccination process ( 38 ).…”
Section: Discussionmentioning
confidence: 64%
“…Nevertheless, this beneficial effect of mTORi after two doses of vaccine was no maintained in the adjusted model in our cohort, findings also noted by Bae ( 33 ). Several authors found similar results with MPA and mTORi in different groups of patients who received two doses ( 33 37 ), even proposing the temporary suspension of treatment during the vaccination process ( 38 ).…”
Section: Discussionmentioning
confidence: 64%
“…In addition, there was a statistically significant relationship between increasing titer categories and proportion with confirmed infection (Wilcoxon rank sum, P = .006) [ 10 ]. It is also worth mentioning that in other cohorts of SOT recipients with BI, patients with negative or non–high-level AbR had a higher risk of unfavorable outcomes in terms of mortality and hospitalization compared with patients with high-level AbR [ 11–13 ].…”
Section: Discussionmentioning
confidence: 99%